TANTANGAN GURU PENDIDIKAN AGAMA ISLAM DALAM MENGHADAPI PERKEMBANGAN DI ERA INDUSTRI 4.0 - Novita Sari (EDURELIGIA: Jurnal Pendidikan Agama Islam, 2020)
In the era of industrial revolution this has an influence on the world of education.  many changes in attitudes experienced by students by incidentally are millennials who are familiar with the digital world and they are familiar with the flow of information and industrial technology 4.0 teachers have a very impⁿortant role to influence the education of students.  especially PAI teachers whose duty is not only to convey knowledge or merely transfer knowledge, but also to be responsible in the moral and moral education of students.  increasingly sophisticated technological developments should be managed positively so as to provide benefits and positive and positive impacts for the advancement of education, especially in the current era of the industrial revolution.